2009
DOI: 10.1111/j.1600-0781.2009.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of low‐energy double‐pass 1450 nm laser treatment for acne in Asians

Abstract: Low-energy, double-pass therapy is an alternative method that is beneficial for patients who complain of considerable pain. Furthermore, the method may have a lower risk of transient hyperpigmentation induced by cryogen spray, even in Asian patients who tend to develop inflammatory pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Practically, the 1450‐nm laser is not being used in the United States because of the amount of pain it caused to patients. However, recent studies have shown that using relatively lower energy with a double‐pass technique as applied in this study is as effective, less painful, and better tolerated, and subsequent studies also confirmed the findings . The level of pain of the double‐pass, low‐fluence DL treatment has been reported to be moderate (visual analogue scale 4.8–5.3/10), which is comparable to or lower than that of non‐ablative fractional laser widely used .…”
Section: Discussionsupporting
confidence: 79%
“…Practically, the 1450‐nm laser is not being used in the United States because of the amount of pain it caused to patients. However, recent studies have shown that using relatively lower energy with a double‐pass technique as applied in this study is as effective, less painful, and better tolerated, and subsequent studies also confirmed the findings . The level of pain of the double‐pass, low‐fluence DL treatment has been reported to be moderate (visual analogue scale 4.8–5.3/10), which is comparable to or lower than that of non‐ablative fractional laser widely used .…”
Section: Discussionsupporting
confidence: 79%
“…153 Several studies have found the 1450 nm diode laser can improve acne and it has been shown to cause sebaceous gland destruction in a rabbit ear model and in ex vivo human skin. [154][155][156][157][158][159] To improve efficacy and reduce side-effects of laser-based treatments, attempts have been made to concentrate the thermal injury to the sebaceous glands while sparing surrounding structures using gold-coated silica and silver microparticles. While a gold-coated silica microparticle suspension is currently marketed in Europe, it is not available in the United States and two recent trials of a topical silver photoparticle compound in conjunction with 810 nm and 1064 nm lasers did not achieve the primary efficacy endpoints.…”
Section: Laser and Light-based Therapies Photodynamic Therapymentioning
confidence: 99%
“…Downtime is minimal and is restricted to temporary erythema, edema, and hyperpigmentation after treatments. 30 This laser achieves mild to moderate improvement of acne scarring in Asian patients without producing permanent pigmentary change even in darker skin types IV and V. 31,32 Nonablative Fractionated Lasers…”
Section: -Nm Diode Laser (Candela Smoothbeam)mentioning
confidence: 99%